Association of gamma-tocopherol serum concentrations and blood pressure among adults in the United States: a cross-sectional study - Wu, Zhijian; Xie, Feng; Li, Kai; Feng, Jie; Han, Leilei; Wu, Yanqing (Frontiers in Cardiovascular Medicine, 2023)
Background hypertension is one of the major preventable risk factors for numerous diseases. The role of vitamin E in blood pressure (BP) has been controversial. We aimed to investigate the relationship between gamma-tocopherol serum concentration (GTSC) and BP Methods Data from 15,687 US adults from the National Health and Nutrition Examination Survey (NHANES) were analyzed. The correlations of GTSC with systolic BP (SBP), diastolic BP (DBP), and prevalence of hypertension were investigated by multivariate logistic regression models, generalized summation models, and fitted smoothing curves. Subgroup analyses were performed to investigate possible effect modifiers between them. Results With each natural log increase in GTSC, SBP, and DBP increased by 1.28 mmHg (β 1.28, 95% CI 0.71–1.84) and 1.15 mmHg (β 1.15, 95% CI 0.72–1.57), respectively, both P for trend < 0.001; the prevalence of hypertension increased by 12% (OR 1.12, 95% CI 1.03–1.22), P for trend 0.008. In subgroup analysis, in drinkers, with each natural log increase in GTSC, SBP, and DBP increased by 1.77 mmHg (β 1.77,95% CI 1.13–2.41) and 1.37 mmHg (β 1.37,95% CI 0.9–1.85), respectively, whereas they were not correlated in non-drinkers. Conclusion GTSC was linearly and positively associated with SBP, DBP, and the prevalence of hypertension, and alcohol consumption may modify the relationship of GTSC with SBP and DBP.